Crecimiento de chame ( dormitator latifrons r.) bajo tres densidades de siembra, con tecnología biofloc - Machuca Valverde, Cristian Andrés (2022)
VII ABSTRACT The chame (Dormitator latifrons R.) is a native species of Ecuador, it represents one of the most interesting aquaculture options to produce, due to its resistance to diseases and its feeding mainly of detritus, however it has only been cultivated in a traditional way, reason why which was proposed this investigation with the purpose of evaluating the growth of chame (Dormitator latifrons R.) under three densities of seeding, with biofloc technology.